Tracing the Footprints of Industrial Dispersal: Evidence from Reports on India’s Industrial Growth Centre Scheme - Ganaie, Ajaz Ahmad; Kaur, Mandeep; Mehra, Anjali (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Industrial Growth Centre (hereafter abbreviated as IGC) scheme, launched in 1988 by the Government of India, aimed to promote balanced regional development by creating well-equipped industrial estates in backward areas. The scheme sought to reduce regional disparities by providing reliable infrastructure such as power, water, roads, communication facilities, and basic institutional support to attract private investment. This study examines the scheme’s objectives, implementation process, funding pattern, and overall performance using secondary data from government reports, evaluation studies, and CAG findings. The results shows major challenges, including delays in planning and approval, slow release of funds, weak land acquisition, poor infrastructure development, and lack of institutional coordination. Although a large amount of money was allocated, the scheme did not fully achieve its goals of industrial dispersal, job creation, and sustainable industrial growth. The study concludes that while the policy vision was strong, poor implementation limited its impact. Better governance, stronger monitoring, and state-specific planning are essential for improving future industrial infrastructure programmes.